Treatment of Intercompany Transfer Pricing for Tax Purposes : A Survey of Legislative and Administrative Issues - Ikeda, Yuichi (IMF Working Papers; Working Paper, 1992)
Tax authorities in several countries have intensified their surveillance of intercompany transfer pricing in recent years. This paper examines the legislative and administrative issues related to the treatment of intercompany transfer pricing for tax purposes. It reviews the existing international guidelines and national rules on methods for determining appropriate transfer prices, as well as the issues related to tax administration practices for the implementation of those rules. Various systems, proposed or introduced to improve the predictability of taxation, are also examined. This paper further reviews the recent discussions on the 'commensurate-with-income' standard and the pricing methodologies proposed thereunder. It finally reviews some alternative approaches to international income allocation which are proposed or adopted in lieu of the transfer pricing approach.